Coordinating Utterances During Turn-Taking: The Role of Prediction, Response Preparation, and Articulation. Issue 2 (17th February 2018) - Corps, Ruth E.; Gambi, Chiara; Pickering, Martin J.
ABSTRACT: During conversation, interlocutors rapidly switch between speaker and listener roles and take turns at talk. How do they achieve such fine coordination? Most research has concentrated on the role of prediction, but listeners must also prepare a response in advance (assuming they wish to respond) and articulate this response at the appropriate moment. Such mechanisms may overlap with the processes of comprehending the speaker's incoming turn and predicting its end. However, little is known about the stages of response preparation and production. We discuss three questions pertaining to such stages: (1) Do listeners prepare their own response in advance?, (2) Can listeners buffer their prepared response?, and (3) Does buffering lead to interference with concurrent comprehension? We argue that fine coordination requires more than just an accurate prediction of the interlocutor's incoming turn: Listeners must also simultaneously prepare their own response.